The Rights of Minorities in the Kurdistan Regional Government (KRG) in light of Multicultural Citizenship Theory - ROUHI, EBAD; BAYZ, HEMIN QASIM (The journal of contemporary issues in business and government, 2021)
Like the other communities in the world, Kurdistan has several different groups which have their own unique identity and cultures. At the same time, in the absence of external intervention, they largely are living peacefully together. The Kurdistan Regional Government (KRG) and the Kurdish sovereignty, within their means and authority, have tried to maintain and promote these peaceful circumstances. Thus, it has taken some practical steps and put some efforts to prove it’s believes in such a peaceful coexistence. It has regarded all the different components and determined their legal and political positions. To promote peace and coexistence every legal effort should be driven by the Constitution of the Kurdistan Region Government (KRG). Kurds who have suffered marginalization, Anfal campaigns and genocides as a minority group within a larger framework, by a dominant culture and people, should take lesson from these experiences when establishing authorities and legal governance ensuring no KRG identify, culture or minority faces this history of suffering. The idea and theory of multicultural citizenship is one of the theories that can become a foundation to protect the ministries’ in any given country which is culturally diverse. Therefore, by accepting Kurdistan as a community with diverse cultural and multi ethnical should consider these differences at time of drafting its Constitution. The Kurdistan Region Constitution, as a modern Constitution, should officially recognize and abide by the principle of multicultural citizenship and on the principle of respecting the differences, and provide the opportunity of meaningful legal and political participation for the majority and minority. Will Kymlicka and Iris Marion Young as two theorists in area of citizenship rights have thoroughly discussed and analyzed the topic of diverse and multicultural citizenship. They have reinforced their theory in relation to the theory of equal citizenship. Thus, they have offered a new legal framework to protect the rights of minorities, which by looking at the cultural form of the KRG using this theory as a principle in the Constitution be useful. Therefore, in this research, this idea would be analyzed in details and would be interpreted in the context of the KRG for drafting a modern Constitution.